Kepemimpinan Situasional sebagai Strategi Kepala Sekolah dalam Meningkatkan Kualitas SDM Pendidikan - Ridwan Hermawan; Istikhori Istikhori; Hasbulloh Karim Alfauzi; Nawil Hadad; Emat Muslihat; Toha Suryana; Khoirul Kusban (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The quality of educational human resources (HR) is a key factor in determining the quality and success of educational implementation in schools. However, many schools still face problems of low performance, motivation, and professionalism among teachers and educational staff due to leadership that is not responsive to the diversity of conditions and human resource needs. This study aims to examine situational leadership as a strategy employed by school principals to improve the quality of educational human resources. The study adopts a literature review approach with qualitative content analysis of books, scholarly journal articles, and relevant previous research. The findings indicate that situational leadership enables school principals to adjust leadership styles directing, coaching, supporting, and delegating according to the levels of readiness, competence, and motivation of teachers and educational staff. Adaptive and participative leadership contributes positively to improved performance, work commitment, professionalism, and the creation of a conducive organizational climate and school culture. Therefore, situational leadership can be used as a strategic approach in planning, implementing, and evaluating sustainable educational quality improvement programs.